Verification of ORM-based Controllers by Summary Inference - Chawla, Geetam; Aman, Navneet; Komondoor, Raghavan; Bokil, Ashish; Kharat, Nilesh (2022 IEEE/ACM 44th International Conference on Software Engineering (ICSE), 2022)
In this work we describe a novel approach for modeling, analysis and verification of database-accessing applications that use the ORM (Object Relational Mapping) paradigm. Rather than directly analyze ORM code to check specific properties, our approach infers a general-purpose relational algebra summary of each controller in the application. This summary can then be fed into any off-the-shelf relational algebra solver to check for properties or specifications given by a developer. The summaries can also aid program understanding, and may have other applications. We have implemented our approach as a prototype tool that works for 'Spring' based MVC applications. A preliminary evaluation reveals that the approach is efficient, and gives good results while checking a set of properties given by human subjects.